2022
DOI: 10.3390/jcs6100297
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Fibre/Metal-Matrix Composites: A Review

Abstract: At present, most carbon fibres are used as reinforcement for polymers. Fabrication technologies for carbon-fibre-reinforced polymers (CFRPs) are now reaching a mature state that effectively replaces metals in various technical fields, including aerospace, sporting equipment, civil engineering, etc. However, there are many structures in which metal alloys cannot be replaced with CFRPs because of, firstly, the limited temperatures that plastics can survive, and secondly, the relatively low fracture toughness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…On the other hand, in an effort to improve the functionality of 3D printing components [30,31], CFs are now largely used in addictive manufacturing processes, opening new technological paths [32]. Therefore, in the present work, the prediction of the damping capacity of the previously analyzed CNOs/α-Ti nanocomposites which are extra reinforced with carbon fibers (CFs) [33][34][35][36][37], is also numerically estimated. It is found that the damping capacity enhancement of the investigated material systems due to the addition of the hollow carbon nanoparticles originates from the higher internal friction of the multilayer graphene-like walls of the CNOs as well as the arisen porosity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in an effort to improve the functionality of 3D printing components [30,31], CFs are now largely used in addictive manufacturing processes, opening new technological paths [32]. Therefore, in the present work, the prediction of the damping capacity of the previously analyzed CNOs/α-Ti nanocomposites which are extra reinforced with carbon fibers (CFs) [33][34][35][36][37], is also numerically estimated. It is found that the damping capacity enhancement of the investigated material systems due to the addition of the hollow carbon nanoparticles originates from the higher internal friction of the multilayer graphene-like walls of the CNOs as well as the arisen porosity.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature review, composites made of carbon-fiber/metal-matrix will be the basis for the breakthrough in aerospace materials. They are high-temperature composites based on refractory metals and high entropy alloys, as well as on intermetallics [130]. Carbon ceramic materials have mostly been recorded to be used as fibers and fillers in metal base matrices creating metal matrix composite materials.…”
mentioning
confidence: 99%